Organism response to load in swimming training - Pupišová, Z.; Franek, V.; Kompán, J. (Slovak Journal of Sport Science, 2021)
The aim of the presented study was to analyze the load of swimmers during a specialized test in the view of changes in selected blood parameters. The research was conducted on junior athletes during the national team camp. 21 swimmers participated in the research, 11 males and 10 females with an average age of 17 ± 1.5 years. Average body height of the swimmers was 179.4 ± 7.72 cm and average body weight was = 66.9 ± 7.46 kg. Measurements were taken before, during and after the 4x200m test by selected swimming stroke of competitor's specialization. Distances were swum by increasing the swimming speed. The results show changes in the values of average times according to the set requirements and current changes in the increase of lactate values and decrease of glucose values after the first section and the subsequent gradual increase of its values after swimming the second, third and fourth section. Based on the results, an individual training load model was set for swimmers.